2023
DOI: 10.1002/adfm.202306534
|View full text |Cite
|
Sign up to set email alerts
|

Materials‐Mediated In Situ Physical Cues for Bone Regeneration

Shuo Liu,
Liguo Zhang,
Zhao Li
et al.

Abstract: Physical cues like morphology, light, electric signal, mechanic signal, magnetic signal, and heat can be used as alternative regulators for expensive but short‐acting growth factors in bone tissue engineering to promote osteogenic differentiation and bone regeneration. As physical stimulation applied directly to the tissue cannot be focused on the bone defect area to regulate the cell behaviors and fate in situ, this limits the efficiency of precise bone regeneration. Biomaterials‐mediated in situ physical cue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 362 publications
0
3
0
Order By: Relevance
“…In contrast to the observations of Ginestra et al [38], based on the particular structuring of the surfaces in this study (0 • and 90 • build orientation) preferential osteoblast settlement was observed in 90 • specimens. This is due to the microstructuring, which has a direct effect on cell-cell interactions [44] and on the actin cytoskeleton and its remodeling, which is associated with direct mechanotransduction, leading to the increased expression of osteogenic markers such as RUNX2, SPP1, and other genes [59][60][61]. In fact, we could detect an upregulation of osteogenic genes with dependence on the build orientation but also with dependence on the niobium content.…”
Section: Discussionmentioning
confidence: 82%
“…In contrast to the observations of Ginestra et al [38], based on the particular structuring of the surfaces in this study (0 • and 90 • build orientation) preferential osteoblast settlement was observed in 90 • specimens. This is due to the microstructuring, which has a direct effect on cell-cell interactions [44] and on the actin cytoskeleton and its remodeling, which is associated with direct mechanotransduction, leading to the increased expression of osteogenic markers such as RUNX2, SPP1, and other genes [59][60][61]. In fact, we could detect an upregulation of osteogenic genes with dependence on the build orientation but also with dependence on the niobium content.…”
Section: Discussionmentioning
confidence: 82%
“…In addition, there existed no pathological abnormalities in the liver and kidney tissues of rats with implantation of piezoelectric membranes and application of US treatment, suggesting the excellent biocompatibility of the therapeutic system discussed above (Figure S7C). Previous efforts have been made to promote macrophage M2 polarization for improved bone regeneration. However, recent works further revealed that sequential macrophage transition based on the temporal immune orchestration would achieve optimized osteogenesis, as overinhibition of initial inflammation would destroy the natural transition of the macrophage phenotype during bone regeneration. Our findings further confirmed that precise control of the M1-to-M2 transition coordinated with a natural process could result in a promising diabetic bone repair outcome. Considering the similar pathological features of other tissue defects, including nerve, skin, and cartilage, under a diabetic background (high ROS accumulation and excessive pro-inflammatory status), application of temporal immunomodulation might also be expanded to other clinical situations.…”
Section: Resultsmentioning
confidence: 99%
“…Bone matrix mineralization vitally affects its hierarchical structure and physical−chemical properties. 25 The biological process of bone matrix mineralization involves the deposition of inorganic components on organic ECM components, mainly occurring in the late stage of osteoblast differentiation. The late stage of osteoblast differentiation is characterized by increased levels of collagen I and by the production of noncollagenous proteins such as BSP, OPN, OCN, and SOST, which are essential in stabilizing the matrix.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroxyapatite (HAP) nanoparticles, as an essential component of the native bone matrix and an FDA-approved drug for the treatment of bone defects, have not been thoroughly investigated for their effect on the development of bone microtissues or bone organoids. Bone microtissues engineered with autologous MSCs and HAP nanoparticles could be considered an autologous bone tissue substitute, facilitating their translation to the clinical setting. It is necessary to explore the formulas for constructing bone microtissues with MSCs and HAP nanoparticles and further evaluate the effect of HAP nanoparticles on the development of bone microtissues.…”
Section: Introductionmentioning
confidence: 99%